Structured exercise program on Foot Biomechanics & Insulin Resistance among people living with type 2 diabetes with and without peripheral neuropathy - Amaravadi Sampath Kumar (Endocrinology Research Centre, 2019)
Background: The biomechanical changes in foot among people with type 2 diabetes mellitus often leads to various foot complications which could further add to diabetes related morbidity & mortality. These changes could be seen due to musculoskeletal factor like reduction in intrinsic foot muscle strength, tightness of lower limb muscles, postural changes, etc. Aim: To design and determine the efficacy of a structured exercise program on foot kinetics and kinematics among type 2 participants Materials and methods: A total of 35 participants with type 2 diabetes (n=15, type 2 diabetes mellitus without neuropathy and n=20, type 2 diabetes with peripheral neuropathy) were recruited. All participants were screened clinically & biochemically and given a set of structured exercise program, three times a week for 12weeks along with standard medical care. Results: The mean age of the participants was 56±10.5 (Non neuropathy) 62.3±7.35 (Neuropathy) years, mean duration of diabetes was 8.7±8.95 (Non neuropathy), 10.97±8 (Neuropathy) years, mean Body mass index was 26.54± 4.83(Non neuropathy), 24.39±3.58 (Neuropathy), Significant differences have been observed in kinetic and kinematic variables. Conclusion: The present study shows that the structured exercise protocol is very effective in improving the biomechanics of foot in people with type 2 diabetes with and without neuropathy. It could help to correct the structure and function of the foot and eventually could reduce the risk of foot complications like diabetic foot ulcers.